Defining the Added Value of 99mTc-MIBI SPECT/CT to Conventional Cross-Sectional Imaging in the Characterization of Enhancing Solid Renal Masses. (April 2017) - Sheikhbahaei, Sara; Jones, Christopher S.; Porter, Kristin K.; Rowe, Steven P.; Gorin, Michael A.; Baras, Alex S.; Pierorazio, Phillip M.; Ball, Mark W.; Higuchi, Takahiro; Johnson, Pamela T.; Solnes, Lilja B.; Epstein, Jonathan I.; et al.
Abstract : Purpose: This study investigates whether the addition of preoperative 99m Tc-MIBI SPECT/CT can increase the degree of diagnostic confidence in the differentiation of benign from malignant enhancing renal masses. Patients and Methods: Patients were recruited as part of an institutional review board–approved prospective clinical trial. Forty-eight patients with clinical stage T1 solid renal masses who underwent a 99m Tc-MIBI SPECT/CT before partial or radical nephrectomy were evaluated. Conventional CT and MRI, which were approximately performed within 8 weeks before 99m Tc-MIBI, were retrospectively retrieved. Based on a 5-point scale (1 = definitely benign, 5 = definitely malignant), 2 blinded readers recorded their degree of confidence for each lesion using conventional imaging before and after reviewing the 99m Tc-MIBI uptake ratios. Surgical pathology was considered as the reference standard. Results: Additional review of 99m Tc-MIBI SPECT/CT uptake ratios increased diagnostic confidence in the differentiation of solid renal masses in 14/48 lesions (29.2%). In 9 lesions, the addition of 99m Tc-MIBI changed the initial confidence levels of malignancy toward benign diagnosis. Postsurgical pathology confirmed the diagnosis of benign histology (oncocytoma/hybrid oncocytic-chromophobe tumors) in 7 and chromophobe renal cell carcinoma (behave as indolent) in 2 of these lesions. 99m Tc-MIBI increased the confidence level toward malignancy in 5 cases; all were confirmed as RCC on surgical pathology. The area under the receiver operative characteristic curve was 0.60 for conventional imaging alone and 0.85 after reviewing 99m Tc-MIBI ( P for difference = 0.03). Conclusions: Preoperative 99m Tc-MIBI SPECT/CT enhances the performance of conventional imaging, improving the characterization of benign histologies and lowering the possibility of misclassification.